Les v mestnem oblikovanju - Zupančič-Strojan, Tadeja (Les (Ljubljana), 1999)
Wood is very important in the process of urban design. It could be used in various combinations of location, programme, form and meaning. It illustrates the story of the way of living in a particular urban place.
Keywords: les; mestno okolje; urbanism; urbanizem; oblikovanje